2022
DOI: 10.3389/fphar.2022.903171
|View full text |Cite
|
Sign up to set email alerts
|

Prunella vulgaris L. – A Review of its Ethnopharmacology, Phytochemistry, Quality Control and Pharmacological Effects

Abstract: Prunella vulgaris L. (PVL) is dried fruit spike of Lamiacea plant Prunella vulgaris L., which is a perennial herb with medicinal and edible homology used for thousands of years. PVL is bitter, acrid, cold, and belongs to the liver and gallbladder meridians. It clears the liver and dissipate fire, improve vision, disperse swelling, and has satisfactory clinical therapeutic effects on many diseases such as photophobia, dizziness, scrofula, goiter, breast cancer. The collection of information and data related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 123 publications
0
24
0
2
Order By: Relevance
“…They are skeletons of 30 atoms of carbon divided in three main types, oleanane, ursane, and lupane, and they may be present in the free, ester, or glycosylated form. In P. vulgaris , oleanolic acid and ursolic acid are pointed as the main triterpenoids ( Figure 2 ) [ 95 , 96 ]. Steroids are also present and are mainly represented by phytosterols and their derived saponins, such as sitosterol and stigmasterol [ 96 ].…”
Section: Pharmacological Wound Healing Evidence Of Iberian Lamiaceaementioning
confidence: 99%
See 2 more Smart Citations
“…They are skeletons of 30 atoms of carbon divided in three main types, oleanane, ursane, and lupane, and they may be present in the free, ester, or glycosylated form. In P. vulgaris , oleanolic acid and ursolic acid are pointed as the main triterpenoids ( Figure 2 ) [ 95 , 96 ]. Steroids are also present and are mainly represented by phytosterols and their derived saponins, such as sitosterol and stigmasterol [ 96 ].…”
Section: Pharmacological Wound Healing Evidence Of Iberian Lamiaceaementioning
confidence: 99%
“…In P. vulgaris , oleanolic acid and ursolic acid are pointed as the main triterpenoids ( Figure 2 ) [ 95 , 96 ]. Steroids are also present and are mainly represented by phytosterols and their derived saponins, such as sitosterol and stigmasterol [ 96 ]. Other sterols have also been identified, such as daucosterol and α-spinasterol [ 95 ].…”
Section: Pharmacological Wound Healing Evidence Of Iberian Lamiaceaementioning
confidence: 99%
See 1 more Smart Citation
“…It is derived from the dried spica of Prunella vulgaris L., an annual herb that flowers and withers in summer, and is widely circulated throughout China. 1 Modern phytochemical and pharmacological researches revealed that the major bioactive components of PS were phenolic acids, flavonoids, triterpenoids and saccharides [2][3][4] that are responsible for wide efficacies, such as anti-tumour, 5,6 anti-oxidative, 7,8 antiinflammatory, 9 anti-bacteria, 10 anti-virus 11,12 and sedative effects. 13 In Chinese Pharmacopoeia (2020 version), rosmarinic acid, a phenolic acid compound, was used as a single qualitative and quantitative marker for the quality control of PS with the specified content more than 0.2%.…”
Section: Introductionmentioning
confidence: 99%
“…It is derived from the dried spica of Prunella vulgaris L., an annual herb that flowers and withers in summer, and is widely circulated throughout China 1 . Modern phytochemical and pharmacological researches revealed that the major bioactive components of PS were phenolic acids, flavonoids, triterpenoids and saccharides 2–4 that are responsible for wide efficacies, such as anti‐tumour, 5,6 anti‐oxidative, 7,8 anti‐inflammatory, 9 anti‐bacteria, 10 anti‐virus 11,12 and sedative effects 13 …”
Section: Introductionmentioning
confidence: 99%